Mechano-thermo-chromic device with supersaturated salt hydrate crystal phase change - Cho, Hyunmin; Kwon, Jinhyeong; Ha, Inho; Jung, Jinwook; Rho, Yoonsoo; Lee, Habeom; Han, Seungyong; Hong, Sukjoon; Grigoropoulos, Costas P.; Ko, Seung Hwan (Science Advances, 2019)
Active control of transparency/color is the key to many functional optoelectric devices. Applying an electric field to an electrochromic or liquid crystal material is the typical approach for optical property control. In contrast to the conventional electrochromic method, we developed a new concept of smart glass using new driving mechanisms (based on mechanical stimulus and thermal energy) to control optical properties. This mechano-thermo-chromic smart glass device with an integrated transparent microheater uses a sodium acetate solution, which shows a unique marked optical property change under mechanical impact (mechanochromic) and heat (thermochromic). Such mechano-thermo-chromic devices may provide a useful approach in future smart window applications that could be operated by external environment conditions.
Keywords: Driving mechanism; Electrochromics; External environments; Liquid crystal materials; Mechanical impacts; Mechanical stimulus; Sodium acetate solution; Thermo-chromic